Bioethics in Latin America: The quality of life of indigenous women. - Munguía-Sánchez, Andrea (2023)
The diversity of indigenous peoples in Latin America includes human relationships, worldview of the world, community life and the conception of the person immersed in a relationship with the land and ecosystems, Latin American Bioethics must respond to the needs of these immersed peoples in poverty, a situation that leaves them in a condition of constant vulnerability, especially indigenous women, who despite having the same dignity, values and responsibilities within their communities, experiment continuous violations of their human rights. They create bonds of solidarity to promote equity as one of the values of Bioethics for the common good.